Combining distance and force measurements to monitor the usage of walker assistive devices - Dias Pereira, J. M. (2018)
This paper presents a measurement system that can be used to monitor the usage of walker assistive devices. The forces applied on the legs of the walker device are measured using low cost force sensing resistors and a light detection and ranging device is used to evaluate several gait kinematic parameters, such as, walking speed and walking stride length. To evaluate the right usage of the walker device two walker indexes, one related with the applied forces and the other related with walker gait phases, are introduced. The measurement system includes wireless communication capabilities that enable a local and remote supervision of the measuring data.